TARogic: Tangible augmented reality game - Tong Lee, Kah; Quek, Albert (International Journal of Engineering and Technology, 2018)
Augmented Reality (AR) has been around for the past decade. It has been applied in many fields and one of the common fields is in education. In this paper, we have make use of Tangible Augmented Reality technology in creating an interactive game called TARogic that teaches students on the basic of programming logics. Tangible Augmented Reality is a combination of Augmented Reality (AR) technology and Tangible User Interface (TUI), which uses real environment objects to interact with the Augmented Reality (AR) environment. In this project, we have created a hardware console that uses USB drive as a tangible element to interact with the game. The USB drive is plug on to the console (Arduino module) to transfer the information of the game input to a smartphone via Bluetooth. The output is displayed on the smartphone in the form of Augmented Reality (AR) game objects and environment. By qualitative user evaluation of two groups of participants, 10 for each groups, 60% of the participants were positive with the overall learning experience using TARogic.Â Â